The Investigation of Identity Crisis in Newly Established Cities of Iraq: A Research on Qaedin and Khawarij - Khakrand, Shokrollah (Journal of History Culture and Art Research, 2017)
The uneven development of Islam after the death of Prophet Muhammad has caused the lack of provision of identity backgrounds for Bedouin majority of Muslims and those of companions who exited the range of Islamic community turned to acquisition of other nations’ identities. This issue has led to many identity crises in Islamic community. These identity disorders have passed a 25-year process at the era of the three caliphs until they reached the crisis level. The peak of these crises started with the killing of Usman and during the reign of the fourth caliph, Ali, was more revealed. Numerous conflicts with other unauthentic Islamic tendencies, blending with the course of identities, the lack of development of critical thinking and recorded identities, and identity gap were of the most important crises that Ali’s reign was faced with. The result of these heterogeneities was the emergence of two dominating groups of Mozabzab (hesitant)-Qaedin (leaders), and Extremist-Khawarij in cities of Kufa. Using the psychological analysis of historical context, in this study, it is tried to answer the questions that: the collective identity crises was the result of what factors? Each group of this society was faced with what kind of crisis? Sheldon Stryker’s theory of identity crisis and Erik Erikson’s theory of growth and identity are used to answer to these questions.